PEMBERDAYAAN MASYARAKAT DUKUH SAWAHAN DESA TELUKAN MELALUI PEMANFAATAN ECENG GONDOK MENJADI PAKAN FERMENTASI UNTUK PAKAN TERNAK KAMBING - Santosa, Sartono Joko; Triyono, Kharis; Maulida, Elly Istiana; Adib, Farhan (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This Community Partnership Program (PKM) aims to empower the community through the use of water hyacinth as fermented feed for goats. Activities were carried out on September 29, 2024 with a focus on improving the village economy and environmental management. The objectives include the application of water hyacinth fermentation technology into nutritious feed and strengthening community independence in providing animal feed. This program also helps reduce water hyacinth populations that disturb aquatic ecosystems. Outputs include fermented feed products, publications in accredited scientific journals, and presentations at national forums. Implementation methods include counseling, technical training, mentoring, and hands-on practice of making feed. To ensure sustainability, regular monitoring and evaluation are conducted. Through a participatory approach, this activity is expected to increase livestock productivity while preserving the environment in the partner area.